FEAR OF FAILURE, PARENT’S SUPPORT, AND STUDY MOTIVATION AMONG STUDENTS IN PESANTREN - Latifah Nur Ahyani; Syaroh Madyaningtyas Asmarani (Proyeksi: Jurnal Psikologi, 2012)
This study was conducted in order to verify relationship among fear of failure, parent’s support andstudy motivation in pesantren’s students. Subjects of research were 32 students from grade XIIPesantren MA NU Banat Kudus and 48 students in Pesantren MA Muhammadiyah Kudus. This was apopulation study, employing study motivation scale, fear of failure scale, and parent’s support scale asmeasurement tools. Data of research were analysed using two predictor regression analysis (anareg),resulted in coefficient correlation number of the three variables = 0,761 whereas thesignificance level was = 0,000 (p<0, 01). This means there is very significant positive correlation amongfear of failure, parent’s support and study motivation among students in the two pesantrens. The morefear of failure and parent’s support, the more study motivation would be, otherwise the less fear offailure and parent’s support, the less study motivation would be. Effective contribution of fear of failureto study motivation was 0, 2%, while effective contribution of parent’s support to study motivation was57, 7%